2016
DOI: 10.1002/adma.201506074
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong Bioinspired Graphene‐Based Fibers via Synergistic Toughening

Abstract: Ultrastrong bioinspired graphene-based fibers are designed and prepared via synergistic toughening of ionic and covalent bonding. The tensile strength reaches up to 842.6 MPa and is superior to all other reported graphene-based fibers. In addition, its electrical conductivity is as high as 292.4 S cm(-1). This bioinspired synergistic toughening strategy supplies new insight toward the construction of integrated high-performance graphene-based fibers in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 31 publications
0
95
0
Order By: Relevance
“…The interface in the nacre induces multiple toughening mechanism, such as mineral bridging, nanoasperities shearing, organic gluing, and tablet interlocking, [1] as shown in Figure 3. [122][123][124][125][126][127][128] In addition, different interface interactions could be reasonably combined to result in synergistic effect, [111,[129][130][131][132][133][134][135][136][137][138][139] which is similar to the multiple interface interactions in nacre. [48,75,[91][92][93][94] The interfacial crosslinking strategies contain hydrogen bonding, [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] ionic bonding, …”
Section: Interfacial Architecture Of Biological Materialsmentioning
confidence: 98%
“…The interface in the nacre induces multiple toughening mechanism, such as mineral bridging, nanoasperities shearing, organic gluing, and tablet interlocking, [1] as shown in Figure 3. [122][123][124][125][126][127][128] In addition, different interface interactions could be reasonably combined to result in synergistic effect, [111,[129][130][131][132][133][134][135][136][137][138][139] which is similar to the multiple interface interactions in nacre. [48,75,[91][92][93][94] The interfacial crosslinking strategies contain hydrogen bonding, [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114] ionic bonding, …”
Section: Interfacial Architecture Of Biological Materialsmentioning
confidence: 98%
“…Invention: Robust-fiber SEM image: reproduced with permission. [15] Copyright 2016, Wiley-VCH; Flexible-membrane SEM image: reproduced with permission. [16] Copyright 2015, American Chemical Society; Ceramic-based nanocomposite SEM image: reproduced with permission.…”
Section: Interface Interactionsmentioning
confidence: 99%
“…Zhang et al [15] demonstrated ultrastrong bioinspired GO fiber composites by introducing synergistic interface interactions of ionic bonding and covalent bonding, as shown in [60] Copyright 2015, Nature Publishing Group. C) Fabrication process of MM-3D-printed nanocomposites: i,ii) addictive 3D printing of ink, iii-vi) applying a magnetic field to align MMT platelets followed by UV-light-induced consolidation, and vii,viii) the final yield of MM-3D-printed nanocomposites.…”
Section: Extension Of Bioinspired Fabricationmentioning
confidence: 99%
See 2 more Smart Citations